ANALISIS EFEKTIVITAS PEMBIAYAAN MURABAHAH DALAM PERTUMBUHAN UMKM DI BMT AL-HIJRAH BUKITTINGGI - Putri Daulay; Gusril Basir (BORJUIS: JURNAL OF ECONOMY, 2025)
Murabahah financing is a form of sharia-based financing carried out through a sale and purchase agreement with an agreed profit margin. This study uses a descriptive qualitative approach, with data collection through interviews, observations, and documentation. The results of the study indicate that murabahah financing at BMT Al-Hijrah Bukittinggi is effective in supporting the growth of MSMEs. This is reflected in the increase in income, expansion of business scale, and business stability of MSME members receiving financing. The implementation of this financing complies with sharia principles, with supervision and monitoring carried out periodically to ensure the use of funds according to purpose. This study concludes that murabahah financing not only plays a role in improving the economy of MSME actors, but also strengthens the contribution of BMT as a sharia financial institution in community- based economic development.